2021
DOI: 10.1093/infdis/jiab481
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Codetection of Haemophilus influenzae and Streptococcus pneumoniae Shapes Respiratory Syncytial Virus Disease Outcomes in Children

Abstract: Background The role of nasopharyngeal bacteria on RSV disease has been underestimated. We measured the frequency and quantitative detection of potentially pathogenic bacteria in the upper respiratory tract of infants with RSV infection over seven respiratory seasons, and their impact on clinical outcomes. Methods Children <2 years old with mild (outpatients; n=115) or severe (inpatients; n=566) RSV infection, and match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…We found that the simultaneous detection of S. pneumoniae and H. influenzae was the most frequent combination, which is in agreement with previous studies [24,25]. On the other hand, only two patients showed the simultaneous co-detection of S. pneumoniae and S. aureus, which has also been previously reported in young children with RSV infections [4]. The negative association between S. pneumoniae and S. aureus appears to be associated with immune-mediated inter-species inferences [24,26,27] and possibly by the nutritional status.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that the simultaneous detection of S. pneumoniae and H. influenzae was the most frequent combination, which is in agreement with previous studies [24,25]. On the other hand, only two patients showed the simultaneous co-detection of S. pneumoniae and S. aureus, which has also been previously reported in young children with RSV infections [4]. The negative association between S. pneumoniae and S. aureus appears to be associated with immune-mediated inter-species inferences [24,26,27] and possibly by the nutritional status.…”
Section: Discussionsupporting
confidence: 93%
“…Aliquots of NPA aspirates stored at −80 °C were used to identify and quantitate four pathogenic bacteria ( Streptococcus pneumoniae , Staphylococcus aureus , Moraxella catarrhalis , and Hemophilus influenzae ) by real time (RT)-PCR with published primers [ 4 ]. Bacterial loads were measured in copies/mL and log 10 transformed for analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 Furthermore, emerging evidence indicates that bacterial superinfections involving the lower respiratory tract are not as infrequent as traditionally reported in infants with RSV infection. 10 Another point of controversy is the potential benefit of systemic corticosteroids. While multiple studies have demonstrated the lack of benefit of steroids in infants with RSV LRTI, 11 their role in bronchiolitis caused by other respiratory viruses is being recognized.…”
mentioning
confidence: 99%